2018
DOI: 10.1080/21623945.2018.1423911
|View full text |Cite
|
Sign up to set email alerts
|

Mirna biogenesis pathway is differentially regulated during adipose derived stromal/stem cell differentiation

Abstract: Stromal/stem cell differentiation is controlled by a vast array of regulatory mechanisms. Included within these are methods of mRNA gene regulation that occur at the level of epigenetic, transcriptional, and/or posttranscriptional modifications. Current studies that evaluate the posttranscriptional regulation of mRNA demonstrate microRNAs (miRNAs) as key mediators of stem cell differentiation through the inhibition of mRNA translation. miRNA expression is enhanced during both adipogenic and osteogenic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Drosha and Dicer are key enzymes involved in miRNA biogenesis. It is known that Dicer and miRNA biogenesis are essential for the adipogenic differentiation and not osteogenic differentiation of the adipose-derived stem cells [51], however, this function is independent of Dicer's role in preventing growth senescence of primary cells [36]. In the present study, there was a sexual dimorphism in the expression levels of Drosha and Dicer with aging.…”
Section: Discussioncontrasting
confidence: 43%
“…Drosha and Dicer are key enzymes involved in miRNA biogenesis. It is known that Dicer and miRNA biogenesis are essential for the adipogenic differentiation and not osteogenic differentiation of the adipose-derived stem cells [51], however, this function is independent of Dicer's role in preventing growth senescence of primary cells [36]. In the present study, there was a sexual dimorphism in the expression levels of Drosha and Dicer with aging.…”
Section: Discussioncontrasting
confidence: 43%
“…miRNAs play an important role in stem cell self-renewal and differentiation as endogenous post-transcriptional regulators (43). Recently, several studies suggested that miRNAs may be involved in MSC chondrogenic differentiation (4446). During the chondrogenic differentiation of MSCs, various miRNAs display differential expression patterns and can regulate the differentiation process by inhibiting the expression of specific target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of AGO2 is underscored in the context of erythrogenesis, where AGO2 is solely expressed 13 . The function of AGO2 in stem cell differentiation to the osteogenic lineage is implicated by the alterations in AGO gene expression 14 . Direct investigation of AGO2 function during MSC differentiation has not been reported.…”
Section: Introductionmentioning
confidence: 99%